Drug abuse prevention campaign of the Philippine National Police in the City of Urdaneta, Pangasinan - Clarion, Bernardo L. (Urdaneta City, Pangasinan : [s.n.], 2002)
This study aimed to assess the present performance level of the PNP in its drug abuse prevention campaign in the City of Urdaneta as perceived by students, teachers, and LGU officials.
Bibliography: pages 64-67.
CHED-La Union
Keywords: Drug abuse